An Isolable Diphosphene Radical Cation Stabilized by Three‐Center Three‐Electron π‐Bonding with Chromium: End‐On versus Side‐On Coordination. (26th June 2018) - Wang, Wenqing; Xu, Cong‐Qiao; Fang, Yong; Zhao, Yue; Li, Jun; Wang, Xinping
Abstract: Two salts (2 and4 ) containing the radical cations of complexed diphosphenes have been isolated and characterized by electron paramagnetic resonance (EPR) spectroscopy, IR spectroscopy, and single‐crystal X‐ray diffraction. The P−P bond is coordinated to the Cr center either in an end‐on (in2 ) or a side‐on (in4 ) fashion. The spin density of the radical is delocalized over the Cr atom and the two P atoms in2 whereas the unpaired electron is mainly localized on the Cr atom in4 . This work provides the first example of a complexed diphosphene radical (2 ) featuring novel three‐center three‐electron (3c‐3e) π‐bonding in the Cr‐P‐P unit, and the first example of a 17 e Cr radical with a side‐on π‐bonded ligand (4 ).